The Capacity to Buffer and Sustain Imbalanced D-Subgenome Chromosomes by the BBAA Component of Hexaploid Wheat Is an Evolved Dominant Trait - Deng, Xin; Sha, Yan; Lv, Zhenling; Wu, Ying; Zhang, Ai; Wang, Fang; Liu, Bao (Frontiers in Plant Science, 2018)
Successful generation of pentaploid wheat (genome, BBAAD) via interspecific hybridization between tetraploid wheat (BBAA) and hexaploid wheat (BBAADD) holds great promise to mutually exchange desirable traits between the two cultivated wheat species, as well as providing a novel facet for evolutionary studies of polyploid wheat. Taking advantage of the viable and fertile nature of an extracted tetraploid wheat (ETW) with a BBAA genome that is virtually identical with the BBAA component of a hexaploid common wheat, and a synthetic hexaploid wheat, we constructed four pentaploid wheats with several distinct yet complementary features, but of which prominently harboring homozygous BBAA subgenomes is a common feature. By using a combined FISH/GISH method that is capable ofenables diagnosing all individual wheat chromosomes, we precisely karyotyped a larger number of cohorts from the immediate progenies of each of the four pentaploid wheats. We found that the BBAA component of hexaploid common wheat possesses a significantly stronger capacity to buffer and sustain imbalanced D genome chromosomes and appears to harbor more structural chromosome variations than the BBAA genome of tetraploid wheat. We also document that this stronger capacity in of the hexaploid BBAA subgenomes behaves as a genetically controlled dominant trait. Our findings bear implications to the known greater than expected level of genetic diversity in, and the remarkable adaptability of, hexaploid common wheat as a staple crop of global significance, as well as in using pentaploidy as intermediates for reciprocal introgression of useful traits between tetraploid and hexaploid wheat cultivars.